Apoptosis and Phagocytosis Activity of Macrophages Infected by Mycobacterium tuberculosis Resistant and Sensitive Isoniazid Clinical Isolates - Farida J. Rachmawaty; Tri Wibawa; Marsetyawan H. N. E. Soesatyo (Universitas Gadjah Mada, 2006)
Mycobacterium tuberculosis (M.tb) is the main causative pathogen that cause the pulmonary tuberculosis. Intracellular M.tb was reported able to induce macrophages apoptosis, which may have crucial role in the regulation of immun response against M.tb infection. As an intracellular bacteria, M.tb able to live and replicate within macrophages. Phagocytosis is the first step to achieved this condition. The induction of macrophages apoptosis by INH resistant and sensitive M.tb clinical isolates, and H37Rv was studied. The macrophages apoptosis level were measured using an Ag-capture ELISA for histone and fragmented DNA (Cell Death Detection ELISAplus, Roche Diagnostic GmBH). Phagocytosis activity also analyzed, after staining using fluorescence dye (AcriFluorTM, Scientific Device Lab.). The results showed that there was no significantly different between INH resistant and sensitive M.tb clinical isolates in respect their ability to induce apoptosis. The phagocytosis activity among the clinical isolates was shown to be strain dependent, and undistinguishable between the Mtb clinical isolates. There was no association between macrophages apoptosis level and the phagocytosis activity. These data suggested that among the virulent Mtb clinical isolates, the ability to induce macrophages apoptosis and phagocytosis were consistently in comparable level.